Shear strength of municipal solid waste - C. Gomes (2014)
The purpose of the paper is to study municipal solid waste (MSW) shear strength parameters of a landfill in the North of Portugal, which were defined by triaxial compression tests. The results emphasize the influence of the strain levels, waste composition and age on the shear strength parameters. It was concluded that the ageing or degradation of the waste, leads to a decrease both in the overall strength and in the "cohesive" resistance, accompanied with a slight increase in the frictional resistance. The observed behaviour is consistent with the MSW composition changes with ageing: (i) an increase of the relative quantity of inert materials and fine fraction and in the amount of granular materials; (ii) a decrease in particle size, in the amount of organic matter, fabrics and plastics and in the amount of materials with sheet and wire forms. The triaxial tests show that the mobilization of the "cohesive" component of resistance occurs more clearly for axial strain levels greater than 15%-20%, which are greater than those required to mobilize most of the frictional component (until axial strain levels in the range of 5% to 15%).